Carbohydrate–PNA and Aptamer–PNA Conjugates for the Spatial Screening of Lectins and Lectin Assemblies. Issue 2 (4th January 2013) - Scheibe, Christian; Wedepohl, Stefanie; Riese, Sebastian B.; Dernedde, Jens; Seitz, Oliver
Abstract Nucleic acid architectures offer intriguing opportunities for the interrogation of structural properties of protein receptors. In this study, we performed a DNA‐programmed spatial screening to characterize two functionally distinct receptor systems: 1) structurally well‐defined Ricinus communis agglutinin (RCA120), and 2) rather ill‐defined assemblies of L‐selectin on nanoparticles and leukocytes. A robust synthesis route that allowed the attachment both of carbohydrate ligands—such as N‐acetyllactosamine (LacNAc), sialyl‐Lewis‐X (sLeX), and mannose—and of a DNA aptamer to PNAs was developed. A systematically assembled series of different PNA–DNA complexes served as multivalent scaffolds to control the spatial alignments of appended lectin ligands. The spatial screening of the binding sites of RCA120 was in agreement with the crystal structure analysis. The study revealed that two appropriately presented LacNAc ligands suffice to provide unprecedented RCA120 affinity (KD=4 μM). In addition, a potential secondary binding site was identified. Less dramatic binding enhancements were obtained when the more flexible L‐selectin assemblies were probed. This study involved the bivalent display both of the weak‐affinity sLeX ligand and of a high‐affinity DNA aptamer. Bivalent presentation led to rather modest (sixfold or less) enhancements of binding when the self‐assemblies were targeted against L‐selectin on gold nanoparticles. Spatial screening of L‐selectin on the surfaces of leukocytes showed higher affinity enhancements (25‐fold). This and the distance–activity relationships indicated that leukocytes permit dense clustering of L‐selectin.